2017
DOI: 10.1287/mnsc.2016.2514
|View full text |Cite
|
Sign up to set email alerts
|

Credit Ratings and Credit Risk: Is One Measure Enough?

Abstract: This paper investigates the information in corporate credit ratings. If ratings are to be informative indicators of credit risk, they must reflect what a risk-averse investor cares about: both raw default probability and systematic risk. We find that ratings are relatively inaccurate measures of raw default probability—they are dominated as predictors of failure by a simple model based on publicly available financial information. However, ratings do contain relevant information since they are related to a meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(73 citation statements)
references
References 63 publications
5
68
0
Order By: Relevance
“…Each month, from January 1992 to December 2012, we use the most recent SDR beta for each firm and sort the stocks 14 For robustness purposes, we follow Hilscher and Wilson (2013) and use the median PD as an alternative proxy for aggregate default risk. Hilscher and Wilson (2013) find that the median PD is highly correlated with the first principal component which explains the majority of variation in PDs across ratings. However, in our large sample of very heterogeneous countries, the median PD can be a rather noisy measure.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Each month, from January 1992 to December 2012, we use the most recent SDR beta for each firm and sort the stocks 14 For robustness purposes, we follow Hilscher and Wilson (2013) and use the median PD as an alternative proxy for aggregate default risk. Hilscher and Wilson (2013) find that the median PD is highly correlated with the first principal component which explains the majority of variation in PDs across ratings. However, in our large sample of very heterogeneous countries, the median PD can be a rather noisy measure.…”
mentioning
confidence: 77%
“…Panel C of Table 5 reports the negative 12 The specification in (1) does not of itself constrain the PD to lie between zero and one. Hilscher and Wilson (2013) argue that this is not a problem, as long as most of the estimated PDs are small (so that (1 − ) ≈ ). Our estimated PDs satisfy this condition.…”
Section: A3 Vix and Aggregate Default Riskmentioning
confidence: 98%
“…Such procedure may be justified on a number of grounds. In their paper, Hilscher and Wilson [16] provide a number of arguments which are not in favour of CRA ratings. Above all, even a very straightforward model developed by logistic regression, based on publicly available information and market indicators, remains superior in comparison to CRA ratings.…”
Section: Modification Of the Sa Approachmentioning
confidence: 99%
“…This can be interpreted as a response to increasing criticism of CRA ratings and their contribution to deepening the negative effects during periods of stress. It was proven that credit ratings are unable to predict the defaults in a proper manner and that they are inferior to the relatively straightforward scoring models which can be developed on the basis of publicly available information [16]. On the other hand, it was evident that certain manipulations had occurred, with respect to reallocation of portfolio in the classes which had been, in the eyes of regulators, perceived as less risky, and which were accordingly treated with lower risk weights.…”
Section: Introductionmentioning
confidence: 99%
“…They found that firms with better CSR scores enjoy higher credit ratings from the same industry and geographical region. However, the use of credit ratings as a proxy for the probability-of-default is not appreciated due to its simplified approach based on publicly available information that does not include information on systematic risk and uncertainty (Hilscher & Wilson, 2013). Furthermore, the use of credit ratings as a proxy for credit risk not only reduces the number of observations but also does not take into consideration the dynamic nature of a firm's behavior over the period.…”
Section: Introductionmentioning
confidence: 99%